Analysis of Influencing Factors of Turnover of the Catering Industry-Taking Catering Industry in Guangzhou as an Example - Tang, Haozhe (International Journal of Global Economics and Management, 2024)
This paper mainly analyzes the key factors affecting the turnover of catering industry enterprises, and conducts empirical research by establishing a regression model. In this paper, taking the turnover of catering enterprises in Guangzhou from 2018 to 2023 as the dependent variable, the regression model was established, and the total number of stores of chain catering enterprises, the number of employees of catering enterprises, the consumption level of residents and the number of urban populations was selected as the independent variables. By building a linear model and collecting data, linear regression analysis using SPSS software, yielded high goodness of fit, but the model with four independent variables had an insignificant effect on the dependent variable. Further stepwise regression analysis showed that only the consumption level of residents and the number of employees in the catering enterprises had a significant impact on the turnover. The final regression model indicated that these two factors had a positive influence on the turnover.